PENGARUH BAURAN PEMASARAN 7P TERHADAP KEPUTUSAN PEMBELIAN MIXUE ICE CREAM & TEA (Studi Kasus di Jalan Usman Sadar Gresik) - Addini, Ananda Yovinta; Vitriya, Rezza (Jurnal Ekonomi dan Kewirausahaan Kreatif, 2024)
Examining how the 7 Ps of marketing—product, price, location, promotion, people, process, and physical evidence—affect consumers' final choices to buy is the primary goal of this study. The focus of this research is Mixue Ice Cream & Tea customers on Jalan Usman Sadar Gresik. One hundred pieces of data were culled from surveys using purposive and non-probability sampling methods. Statistical test version 26 was used for data analysis, specifically multiple linear regression analysis. Location and promotions did not have a significant impact on buying choices for Mixue Ice Cream & Tea, according to the t test findings. On the other hand, product, pricing, people, process, and physical evidence all had positive and significant influences. Product, pricing, location, marketing, people, process, and physical evidence all play a role in determining whether or not someone buys Mixue Ice Cream & Tea, according to the f test findings.